Home Optical Coherence Tomography Monitoring for Neovascular Age-Related Macular Degeneration: Transformative Technology or Cool Toy? - Ethan T. Willis; Judy E. Kim; Eric W. Schneider (Ophthalmology and Therapy, 2024)
Abstract The pending introduction of home-based optical coherence tomography (OCT) in managing neovascular age-related macular degeneration (nAMD) has sparked interesting debates. Advocates assert that home-based OCT will revolutionize care of patients with nAMD, while skeptics question its real-world viability and point out its potential drawbacks. This article delves into the dichotomy, presenting the "pro" argument highlighting the transformative potential of home OCT and the "con" perspective, which scrutinizes the limitations and challenges to adapting the technology to the real-world setting. By exploring both sides of the discourse, we aim to address the promises and complexities surrounding the role of home OCT in the management of nAMD.